Bulk etch rates of CR-39 nuclear track detectors over a wide range of etchant (NaOH aqueous solution + ethanol) concentrations: measurements and modeling. Issue 11 (1st November 2020) - Awad, E.M.; Rana, M.A.
Abstract : Bulk etch rates for CR-39 detector were measured and studied over a wide range of NaOH aqueous solution concentrations (2–20 N) with different ethanol volumes. This wide range of etching concentration is divided into two major parts: soft etching part (2–8 N NaOH) and dense etching part (8–20 N NaOH). This classification will be explained and discussed. The etchant viscosity in the two parts was measured and compared. The effect of ethanol in both parts was deduced through a new parameter called 'reduced bulk etch rate'. This new parameter helps in analyzing the dependence of bulk etching on the amount of ethanol in the etchant. It was found that conducting the etching process in the dense etching part reduces the etching time significantly. Etching in the dense part is not far away from equilibrium where Mushtaq, Multi-hit and Arrhenius fitting equations are applicable. The fitting of measured bulk etching data was carried out in the soft (low), dense (high) and the whole etching concentration ranges. Generally, a good agreement was found between physical data and model calculations.